Elastic intramedullary nailing in unstable fractures of the paediatric tibial diaphysis: A systematic review - Swindells, Mark G.; Rajan, R. A. (Journal of children's orthopaedics, 2010)
Purpose The majority of paediatric tibial fractures can be managed conservatively. However, there is a small but significant group of patients that require surgical intervention for several indications, most notably, unstable fractures. There are various surgical options, each with its own advantages and risks. This review establishes the current available evidence for the use of elastic intramedullary nails in this group. Methods A systematic review of the currently available literature was performed. The relevant studies were then critically appraised. Results Seven applicable retrospective case series were identified, with the outcomes from a total of 210 (range 16–60) patients considered. The mean time to union ranged from 7 to 21 weeks. Reported complications included small numbers each of delayed union, non-union, malunion, leg length discrepancy and infection. Conclusions There is only a small body of evidence currently published on this topic. The evidence published so far concludes that elastic intramedullary nailing represents an effective and reliable method to treat an unstable fracture of the tibial diaphysis in the paediatric patient, where conservative management is not appropriate.